Geriatric Oncology Research in the Cooperative Groups: A Report of a SIOG Special Meeting - Hurria, Arti (2010)
PURPOSE: The purpose of this meeting was to bring together geriatric oncology researchers in the cooperative groups to discuss the design of clinical trials to improve our knowledge of the efficacy and toxicity of cancer therapeutics in older adults with cancer. DESIGN: Meeting of cooperative group leaders in geriatric oncology research RESULTS: Several strategies were suggested to improve our knowledge of the efficacy and toxicity of cancer therapeutics in older adults. These include: 1) developing therapeutic studies for older adults who are not eligible for standard clinical trials (because of comorbidity or functional status), or for patients who are deemed to be at high risk for toxicity from standard therapy (frail or vulnerable); 2) identifying the age group of older adults who are underrepresented on clinical trials and developing trials specifically for these patients; 3) designing trials to include a certain proportion of older adults for subset analyses; and 4) including a geriatric assessment in therapeutic clinical trials in order to identify factors other than chronologic age that identify those older adults who are “vulnerable” (at risk for toxicity) and “fit” (able to tolerate cancer therapy without significant toxicity). CONCLUSIONS: To address knowledge gaps in geriatric oncology, national and international cooperative group leaders discussed strategies in clinical trial design to improve the evidence-based research and accrual of older adults. Linking the efforts among cooperative groups will expedite this progress, and this conference was a major first step toward this goal.